Total endoscopic excision of branchial cyst in a child aged 3 years - Ramakrishnapillai Padmakumar; Madhukara Pai; Mary Varghese; P.G. Shaji; Sayooj K. Mukundan; T.S. Anithadevi (Elsevier, 2017)
This is the case report of a three-year-old female Arab child who presented with a neck swelling since one year of age. Physical examination was suggestive of a 6 × 4 cm swelling in the right lateral neck, which was dumbbell shaped, deep to sternocleidomastoid muscle on either side of the muscle. Ultrasound scan revealed a large cyst with internal echoes in the right carotid space anteriorly. The cyst was dissected endoscopically by an axillary approach and complete excision was achieved, thus avoiding the need for a large incision in the neck. No complications noted after treatment. The lowest age at which branchial cyst excision was carried out endoscopically was 18 years as per the available literature. Hence this case seems to be the first ever endoscopic branchial cyst excision in the pediatric age group.